SOUTH AFRICA AND THE WAR AGAINST JAPAN 1941-1945 - W.M. Bisset (Scientia Militaria, 2012)
Although South Africa was never attacked by Japan during the Second World War, the threat was considered to be so great that one of our most distinguished soldiers, Brigadier (later Major General) W.H. Evered Poole was recalled from the Western Desert on 26 May 1942 and appointed Fortress Commander at The Castle in Cape Town. South Africa's published Official Histories of the Second World War contain few details of South Africans who served in the Far East. Commander H.R. Gordon-Cumming's unpublished Official History of the SA Naval Forces in the Second World War 1939-1945 includes narratives of the two South African ships which served in the Far East, HMSAS BARBRAKE and HMSAS NATAL, and HMS TEVIOT and HMS SALVESTOR which were manned by the South African Naval Force (SANF).